ORAL MANIFESTATION OF RENAL OSTHEODISTROPHY IN CHILDREN - Iuliana Magdalena Stârcea; Anca Ivanov; Adriana Mocanu; Vasile Valeriu Lupu; Mirabela Subotnicu; Mihaela Munteanu; Ancuţa Ignat; Ingrith Miron (Romanian Society of Oral Rehabilitation, 2018)
Very rare in children, the brown tumor, or osteoclastoma, is an understudied ectopic entity that causes severe debilitation in patients with chronic renal insufficiency. We report two cases who developed particular forms with different evolutions of severe renal osteodystrophy.